2018
DOI: 10.1038/s41598-018-28676-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Systematic Ticagrelor-Based Dual Antiplatelet Therapy to Selective Triple Antithrombotic Therapy for Left Ventricle Dysfunction Following Anterior STEMI

Abstract: Antithrombotic management of STEMI patients with apical dysfunction, but without demonstrable thrombus, is controversial. Triple antithrombotic therapy (TATT, defined as the addition of oral anticoagulation to dual antiplatelet therapy, or DAPT) may be associated with increased bleeding, while DAPT alone may not adequately protect against cardio-embolic events. We undertook a dual-center study of anterior STEMI patients treated with primary PCI (pPCI) from 2013 to 2015 and presenting presumed new apical dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…103 A study comparing a treatment strategy of ticagrelor-based DAPT at 1 hospital with triple antithrombotic therapy at another hospital in patients treated with primary PCI for anterior STEMI with “apical dysfunction” found no difference in a composite end point of ischemic and bleeding events, although only 1 patient in the study had a stroke or TIA. 104 There are overall insufficient high-quality study data to assess whether DAPT alone has any protective effects for the formation of LV thrombus or whether a more potent P2Y 12 inhibitor such as ticagrelor might be preferable if DAPT alone is used to treat patients at risk of LV thrombus formation.…”
Section: Dapt For the Prevention Of LV Thrombusmentioning
confidence: 99%
“…103 A study comparing a treatment strategy of ticagrelor-based DAPT at 1 hospital with triple antithrombotic therapy at another hospital in patients treated with primary PCI for anterior STEMI with “apical dysfunction” found no difference in a composite end point of ischemic and bleeding events, although only 1 patient in the study had a stroke or TIA. 104 There are overall insufficient high-quality study data to assess whether DAPT alone has any protective effects for the formation of LV thrombus or whether a more potent P2Y 12 inhibitor such as ticagrelor might be preferable if DAPT alone is used to treat patients at risk of LV thrombus formation.…”
Section: Dapt For the Prevention Of LV Thrombusmentioning
confidence: 99%
“…Studies have also shown that rivaroxaban based antithrombotic regimens can reduce total bleeding events, including events other than the first event in patients with AF who receive antiplatelet therapy after PCI. 24 , 25 Brunetti, ND et al performed a meta-analysis that included patients with NVAF treated with PCI and assessed all bleeding risks 26 : compared with patients receiving the three groups of standard treatment, patients who received rivaroxaban or dabigatran had a significantly lower risk of bleeding. The above results are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%